Process analysis and optimisation for a sustainable circular economy - Cassendra P.C. Bong; Yee Van Fan; Chew Tin Lee; Jiří Jaromír Klemeš (Cleaner Engineering and Technology, 2022)
A sustainable circular economy could be generally achieved via process analysis and optimisation. The circular system or design has to be optimised based on sustainability (economically, environmentally and socially) rather than focus on the degree of circularity in the view that circular is not equivalent to sustainable. The articles that compose this Virtual Special Issue (VSI) provide an overview of process analysis and optimisation works that could contribute to a sustainable circular economy. The selected articles ranged from energy, water, and solid waste recovery to negative emission technologies-related topics.